Free Digital Learning for Inclusion of Migrants and Refugees in Europe: A Qualitative Analysis of Three Types of Learning Purposes - Castaño-Muñoz, Jonatan; Colucci, Elizabeth; Smidt, Hanne (International Review of Research in Open and Distributed Learning, 2018)
The increasing number of migrants and refugees arriving in Europe places new demands on European education systems. In this context, the role that free digital learning (FDL) could play in fostering inclusion has attracted renewed interest. While the existing literature highlights some general design principles for developing FDL for migrants and refugees, there is little information on the use of FDL at specific education levels, or for specific learning purposes. This paper presents the results of a qualitative study that was carried out as part of the Moocs4Inclusion project of the Joint Research Centre (JRC) between July and December 2016. The study, which has a European focus, disaggregates the analysis of FDL initiatives by what were identified as its three most common purposes: a) language learning, b) civic integration and employment, and c) higher education. For each of these topics, the study sheds light on the approaches used by a wide sample of initiatives, users’ levels of awareness of what is available and take up, and migrants’ and refugees’ perceptions of the current offer. In order to collect the information needed to cover different approaches and perspectives, semi-structured interviews with 24 representatives of 10 FDL initiatives and four focus groups with 39 migrants and refugees were carried out. The results show that there are indeed overlaps between the purposes of FDL initiatives and their design principles. Specific recommendations on how to better design FDL initiatives for migrants and refugees, taking into account their specific purposes, have also been identified.